Prevalence of HIV-2 among persons attending Integrated Counselling and Testing Centre at Gandhi Hospital - V Sudha Rani1 , Nirmal Kumar Saxena2 (Perspectives In Medical Research, 2018)
Objective: To study the prevalence of HIV-2 at Gandhi hospital Secunderabad. Materials & Methods: 2765 serum samples collected between April 2008 and March 2009 from persons attending Integrated Counselling and Testing Centre (ICTC) were screened for HIV by Combaids.HIV reactive sera were further tested by Retroquic and Enzyme immunoassay. Results: Out of 2765 serum samples tested, 541 samples were positive for HIV-1, 14 (2.6%) were positive for HIV-2, 11 samples (2.03%) were positive for HIV-2 alone and 3(0.55%) were positive for HIV-1&2. All of them were confirmed by Retroquic and Enzyme immunassay. Conclusion: HIV-2 infection is not uncommon in Secunderabad, which being a cosmopolitan city, there is movement of population. Though the epidemic of HIV-1 is progressing faster than that of HIV-2, monitoring of HIV-2 epidemic is also essential to determine the extent of problem in India. Close monitoring is necessary in all regions of the country so that blood donor screening for both HIV-1 & 2 can be instituted in areas where HIV-2 becomes prevalent